Fundamentos jurídicos de la educación en derechos humanos - Vogelfanger, Alan (2023)
The goal of this paper is to provide the Buenos Aires'educational community in general, and teachers in particular, with a legal justification to educate in human rights. Not every person involved in education istruly aware of their obligation to educate in human rights. Consequently, gathering international, regional, national and sub-national laws recognizing this right to receive human rights education (and, thus, affirming the State?s obligation to ensure every person receives it) is a way ofraising awareness about this crucial issue. Additionally, one can evenfind teachers that are afraid to educate in human rights because theyfeel they are deviating from their jobs, and that families or school authorities could reprehend them. So, not only many persons do not know about their obligation to educate about human rights, but also some people think that when they do it, they are doing something they arenot supposed to, or that they are moving away from their duties. Insteadof considering human rights education as a pillar of their jobs, some teachers feel they might be doing something wrong. Therefore, this compilation of instruments should serve as a tool for teachers to justify andexplain why they are educating in human rights, so they feel that the law is on their side, and that there are legal foundations for what they are doing: it?s not that they are doing something wrong or deviating from their duties, on the contrary, they are actually doing what they are supposed to do